Numerical Modeling and Experimental Investigation of Spray Combustion Process in Regenerative Liquid Propellant Mortar. Issue 2 (14th December 2022) - Liu, Ning; Sun, Mingliang; Shen, Yanping
Abstract: Regenerative liquid propellant guns (RLPGs) have been studied for many years. However, the presence of large pressure oscillations is observed in almost each RLPG firing. In order to push forward the liquid propellant application in guns, a low pressure firing system called regenerative liquid propellant mortar (RLPM) is developed. The multiphase multidimensional fluid‐dynamics model is presented to research the interior ballistic properties of RLPM. A high‐speed liquid sheet spray model is presented for the annular jet in RLPM based on the linear stability analysis and surface wave breakup theory. In addition to the jet atomization, the droplets secondary breakup is considered. The experiments on a 60 mm RLPM test fixture are carried out, and the results indicate that the liquid propellant combustion oscillations are effectively suppressed. The spray and combustion processes have been simulated for the 60 mm RLPM which are in agreement with the experimental data well. Numerical results indicate an important benefit for the RLPM that the muzzle velocity is improved by increasing the charge quantity while the maximum chamber pressure remains unchanged. Abstract :